PENGGUNAAN MODEL PROBLEM BASED LEARNING BERBANTUAN AUGMENTED REALITY DALAM MENINGKATKAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV - Surya Perdana, Ricky; Yulistia, Annisa; Nurjanah, Siti; Khairani, Fadhilah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low critical thinking skills of fourth-grade students at SD Negeri 10 Metro Timur. This study aims to determine the effect of the augmented reality-assisted problem-based learning model on students' critical thinking skills. The method used in this study is a quasi-experimental design with a non-equivalent control group design. The population consists of 35 students in grades IV A and IV B, and the sample was determined using saturated sampling technique. Data collection was conducted through critical thinking skills tests. The data were analyzed using simple linear regression tests. The results of this study indicate that there is a significant effect of the application of the augmented reality-assisted problem-based learning model on the critical thinking skills of fourth-grade students in elementary school IPAS subjects, as shown by a sig value of 0.001 < 0.005.